When Media Are New: Understanding the Dynamics of New Media Adoption and Use - Martin C.J. Elton; John Carey (University of Michigan Press, 2010)
The world of communication media has undergone massive changes since the mid-1980s. Along with the extraordinary progress in technological capability, it has experienced stunning decreases in costs; a revolutionary opening up of markets (a phenomenon exemplified by but not limited to the rise of the Internet); the advent of new business models; and a striking acceleration in the rate of change. These technological, regulatory, and economic changes have attracted the attention of a large number of researchers, from industry and academe, and given rise to a substantial body of research and data. Significantly less attention has been paid to the people who use new media—whose own rate of adoption and assimilation often lags notably behind the technologies themselves. When Media Are New addresses this research and publishing gap by investigating the human factors involved in technological change and their implications for current and future media. It will find a broad audience ranging from media and communication scholars to historians and organizational theorists to industry professionals.